История заселения сел и деревень Завьяловского района - Дмитриев Василий Петрович
Экземпляры: УКП (20130123) / Инвентарный номер: АП20100435 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: Д 53 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)